Simpulan Bahasa, Conceptual Metaphors and Malay Knowledge - Hashim, Mohamad NorTaufiq Nor; Ghani, Aniswal Abd (Pusat Pengajian Ilmu Kemanusiaan, 2019)
This study will be focusing on Malay proverbs. To be exact, it deals with Malay Simpulan Bahasa. Za'ba (2002: 157) states that the “idiom” is also referred to as an ‘expression’, and the meaning of each idiom is conveyed by the combination of the two or more words that are fixed and structurally place in a special arrangement. The data in this study is taken from only one secondary source which is Kamus Bunga Bahasa (1961). The Simpulan Bahasa (SB) chosen for this study consist of only two-word figurative fixed formations. The objective of this study is to show how the meaning of the selected SB can be disambiguated using the Interactive Metaphorical Theory by Black (1962) and Cognitive Semantic Theory by Lakoff and Johnson (1980; 2003). According to Tenas Effendy (2003), many among the Malays today do not understand Malay proverbs. Nor Hashimah and Junaini (2010) also state that almost 60 percent of teens in Malaysia are unable to understand and master the SB well.